If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)(x-2)(x+1)+3(x-2)(x+1)=(x-2)
We move all terms to the left:
(x-2)(x-2)(x+1)+3(x-2)(x+1)-((x-2))=0
We multiply parentheses ..
(+x^2-2x-2x+4)(x+1)+3(x-2)(x+1)-((x-2))=0
We calculate terms in parentheses: -((x-2)), so:We get rid of parentheses
(x-2)
We get rid of parentheses
x-2
Back to the equation:
-(x-2)
(+x^2-2x-2x+4)(x+1)+3(x-2)(x+1)-x+2=0
We multiply parentheses ..
(+x^2-2x-2x+4)(x+1)+3(+x^2+x-2x-2)-x+2=0
We add all the numbers together, and all the variables
(+x^2-2x-2x+4)(x+1)+3(+x^2+x-2x-2)-1x+2=0
We multiply parentheses
(+x^2-2x-2x+4)(x+1)+3x^2+3x-6x-1x-6+2=0
We add all the numbers together, and all the variables
3x^2+(+x^2-2x-2x+4)(x+1)-4x-4=0
We move all terms containing x to the left, all other terms to the right
3x^2+(+x^2-2x-2x+4)(x+1)-4x=4
| 2(53x)=85–2x | | -2(5-3x)=1/2(8x+10) | | 10-(y-6)-y=0 | | 18-6=2/3y | | 5u=200 | | 12x+5=12x+6 | | 3(x-2)+5=2(5×-4) | | 1/4k-k-1/2=1/8k+1/4 | | |2x+2|=|x+18| | | 2x(22x^2-5x-6)=0 | | 2(x+5)+9=2x+5 | | 6(x-2)=36-10× | | 5(2c+7)-4c=7(c+4) | | 9+y=31/3 | | 8^3x=98 | | 9(x+4)=3(12+3x) | | 24=x/5+6 | | 3x-5=19x+7 | | -9(t+18)=4(t-15) | | 2(11d-3)=78+16d | | 8s+1=-5s+66 | | −2x+4=14 | | 7(b+2)–4b=2(b+10) | | 3n+4=2n-1 | | -3(6v-3)=-18v-9 | | 1/3x=-2x+14 | | G(x)=3+2 | | y-(-34)=25 | | 6/11=x/33 | | 3=k+11.5 | | 3(×—2)÷5(2—x)=16 | | y-(-35)=25 |